Acute and chronic diabetes complications associated with self-reported oral health: a retrospective cohort study - Kamini Kaura Parbhakar; Laura C. Rosella; Sonica Singhal; Carlos R. Quiñonez (BMC, 2020)
Abstract Background Oral health is associated with diabetes, but the chances of experiencing acute or chronic diabetes complications as per this association is unknown in Canada's most populous province, Ontario. This study assesses the impact of self-reported oral health on the likelihood of experiencing acute and chronic complications among a cohort of previously diagnosed diabetics. Methods A retrospective cohort study was conducted of diabetics (n = 5183) who participated in the Canadian Community Health Survey 2003 and 2007-08. Self-reported oral health status was linked to health encounters in electronic medical records until March 31, 2016. Multinomial regression models determined the odds of the first acute or chronic complication after self-report of oral health status. Results Thirty-eight percent of diabetics reporting "poor to fair" oral health experienced a diabetes complication, in comparison to 34% of those reporting "good to excellent" oral health. The odds of an acute or chronic complication among participants reporting "poor to fair" oral health status was 10% (OR 1.10; 95% CI 0.81, 1.51) and 34% (OR 1.34; 95% CI 1.11, 1.61) greater respectively, than among participants experiencing no complications and reporting "good to excellent" oral health. Conclusion Self-reporting "poor to fair" oral health status is associated with a greater likelihood of chronic complications than acute complications. Further research regarding the underlying causal mechanisms linking oral health and diabetes complications is needed.